Penggunaan Metode RACH (Rekreasi Alam dan Catatan Harian) dalam Meningkatkan Kemampuan Menulis Teks Deskripsi Kelas VII di SMPN 3 Madiun - Devi Nurfitasari; Dwi Rohman Soleh; Herman Trisna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low descriptive writing proficiency of seventh-grade students at SMPN 3 Madiun. Preliminary observations revealed that students struggled to develop ideas, select descriptive vocabulary, and construct coherent, engaging paragraphs. The study aimed to improve descriptive writing skills through the use of the RACH method (Nature Recreation and Daily Journaling). It employed a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, conducted over two cycles. The subjects were 32 seventh-grade students (first semester) at SMPN 3 Madiun. The research process involved planning, action implementation, observation, and reflection. Data collection techniques included observation, descriptive writing tests, and documentation. Data were analyzed using both quantitative and qualitative descriptive methods. The results indicate that the RACH method effectively improved students' descriptive writing skills. The average score rose from 67.2 in the pre-cycle stage to 75.6 in Cycle I and further to 84.3 in Cycle II. Additionally, students' active participation and learning motivation increased during the learning process. It can be concluded that the RACH method is effective for enhancing the descriptive writing skills of seventh-grade students at SMPN 3 Madiun. This method provides a more tangible, creative, and enjoyable learning experience, thereby helping students express their ideas more easily and systematically. Keywords: RACH method, descriptive text, writing skills, classroom action research.